Crack Propagation in a Toughened Epoxy Adhesive under Repeated Impacts - Ian A. Ashcroft; Vadim V. Silberschmidt; Benjamin Echard; Juan Pablo Casas Rodriguez (Shock and Vibration)
Adhesives are being increasingly used in structural applications, especially in aerospace, automotive and naval structures, making their structural integrity an important issue. In-service loading histories of such structures usually contain low-energy impacts, repetition of which can significantly affect their performance. This paper deals with the behaviour of the toughened epoxy adhesive FM73 under repeated impacts, known as impact fatigue. Izod impact fatigue tests were performed on FM73 specimens in order to study the evolution of damage and to characterise this via measurable parameters, such as the maximum force and the contact time. A finite element model was developed to simulate the impact tests and this was used to calculate the dynamic strain energy release rate, which was compared with that determined using a simple analytical method. A relationship between the maximum dynamic strain energy release rate and impact fatigue crack growth rate was established that was used as the basis of an impact fatigue crack growth law.